From playground extremism to neo-Nazi ideology: Finnish educators' perceptions of violent radicalisation and extremism in educational institutions - Vallinkoski, Katja; Benjamin, Saija (JSSE - Journal of Social Science Education, 2023)
Purpose: The role of formal education is currently viewed as central in preventing violent radicalisation and extremism (VRE), however educators' understanding, or competences have not been developed accordingly. Therefore, this study critically investigates Finnish educators' perceptions of presumed manifestations of VRE among their students. Findings: Finnish educators confront ideologically and morally challenging situations, some of which include extremist features. They do, however, have difficulties in distinguishing VRE from other types of motives for hostile or violent rhetoric or behaviour, especially if students from societal minority groups are involved. Practical implications: False labeling may have negative consequences on students. Educators' need VRE-related in-service trainings that focus on increasing educators' knowledge and reflection on their VRE-related preconceptions and intuitive responses to these. Research limitations: We acknowledge the possible skewedness of the survey data as responding may have felt more appealing to those educators who have encountered VRE or who are interested or worried about VRE.